Kajian Pertumbuhan Penduduk Terhadap Ketersediaan Sarana Dan Prasarana Sosial Ekonomi Di Kecamatan Grogol KabupatenSukoharjo Tahun 2010 Dan 2014 - Wulandari, Ika Listia; , Drs. Priyono, M.Si (2016)
This research is done in Grogol District, Sukoharjo Regency. The purpose of this research is (1) reviewing resident growth level and demography factor which the most influential towards resident growth in Grogol district on 2010 and 2014. (2) reviewing the effect of resident growth toward availability of social economic facilities and infrastructure in Grogol District. The used method on this research is: (1) secondary data, secondary data that used is time series data with comparison of year 2010 and 2014. (2) The used data analysis is descriptive statistical analysis, analysis has done by take scoring or giving score 1 to 3 toward research variables and to analyze the factors which affect resident growth using CBR formula (Crude Birth Rate), CDR (Crude Death Rate) and Mn (MigrasiNeto), while for searching relation of resident growth with availability of social economic facilities is using multiple linear regression formula with SPSS program. The result of this research showing that resident growth in research area year 2010 and 2014 include on low category with percentage 0,71%. The most influence factor of resident growth in Grogol District on year 2010 and 2014 is dead factor, because from dead's number that increase from year 2010 is 4,40 thousandth to year 2014 is 5,68 thousandth. Calculation on year 2010 for relations between resident growth with education facilities R value (0,370) means that R value having low number, relations between resident growth and health facilities R value (0,200) means that Rvalue having very low number, relations between resident growth with economic facilities R value (0,500) means that R value having medium number, while calculation on year 2014 for relations between resident growth with education facilities R value (0,467) means that R value having medium number, relations between resident growth with health facilities R value (0,438) means that R value having medium number and relations between resident growth with economic facilities value R (0,729) means that R value having strong number. Keyword: resident growth, Birth, Death , and Migrasi.